2016
DOI: 10.1039/c5sc04612b
|View full text |Cite
|
Sign up to set email alerts
|

On the prevalence of bridged macrocyclic pyrroloindolines formed in regiodivergent alkylations of tryptophan

Abstract: Brønsted acid promotes internal cinnamylations of tryptophan to form structurally complex pyrroloindolines within unique collections of ansa-bridged composite macrocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…For those studies to be successful, predicted binding interactions will need to be experimentally validated. Our prior experimental results suggest a majority of macrocyclization reactions simulated by CPMG will proceed (15)(16)(17)(18)(19)(20). In a series of studies, we demonstrated that the phenol of tyrosine and the indole of tryptophan react internally with the cinnamyl carbocation-regardless of the 1.…”
Section: Chemistry Biophysics and Computational Biologymentioning
confidence: 84%
See 3 more Smart Citations
“…For those studies to be successful, predicted binding interactions will need to be experimentally validated. Our prior experimental results suggest a majority of macrocyclization reactions simulated by CPMG will proceed (15)(16)(17)(18)(19)(20). In a series of studies, we demonstrated that the phenol of tyrosine and the indole of tryptophan react internally with the cinnamyl carbocation-regardless of the 1.…”
Section: Chemistry Biophysics and Computational Biologymentioning
confidence: 84%
“…distance between reacting positions in acyclic precursors (17,19). Heterocycles shown at the top of Fig.…”
Section: Chemistry Biophysics and Computational Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of such molecules are tetrahydro‐β‐carbolines, obtained from starting indole derivatives or heterocyclic systems obtained by oxa‐Pictet‐Spengler reactions …”
Section: Introductionmentioning
confidence: 99%